2009
DOI: 10.1021/ja907355a
|View full text |Cite
|
Sign up to set email alerts
|

Excited-State Dynamics of Cytosine Tautomers

Abstract: We report the relaxation dynamics of keto and enol or keto-imino cytosine, photoexcited in the wavelength range of 260-290 nm. Three transients with femtosecond to hundreds of picoseconds lifetimes are observed for the biologically relevant keto tautomer and are assigned to internal conversion and excited-state tautomerization. Only two transients with femtosecond and picosecond lifetimes are identified for the enol or keto-imino tautomer and are assigned to internal conversion processes. The results are discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
161
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(182 citation statements)
references
References 37 publications
(94 reference statements)
16
161
5
Order By: Relevance
“…The molecular structure of this minimum is close to the ( 1 π N8 π*/gs) CI structure, but the S 0 and S 1 energies exhibit a large energy gap of about 1.5 eV. Based on this result, Kosma et al 7 attributed the long-time component of τ > 19 ps observed in their experimental spectra to a population trap in the S 1 minimum. However, our calculations contradict this assumption, and instead show that an extremely efficient deactivation pathway exists for the imino form.…”
Section: Deactivation Pathway To ( 1 π N8 π/Gs) CImentioning
confidence: 72%
See 4 more Smart Citations
“…The molecular structure of this minimum is close to the ( 1 π N8 π*/gs) CI structure, but the S 0 and S 1 energies exhibit a large energy gap of about 1.5 eV. Based on this result, Kosma et al 7 attributed the long-time component of τ > 19 ps observed in their experimental spectra to a population trap in the S 1 minimum. However, our calculations contradict this assumption, and instead show that an extremely efficient deactivation pathway exists for the imino form.…”
Section: Deactivation Pathway To ( 1 π N8 π/Gs) CImentioning
confidence: 72%
“…The pump-probe ionization spectrum by Kosma et al 7 can also be interpreted basically in the same way. As mentioned in the Introduction, there is one notable difference from the experiments by Ho et al 8 ; Kosma et al 7 observed another slow component of the decay with lifetime in the range from 19 up to ≥ 150 ps.…”
Section: E Comparison With Experimental Findingsmentioning
confidence: 83%
See 3 more Smart Citations